Analisis Karakteristik Marshall dengan Memanfaatkan Lignin sebagai Pengganti Filler pada Campuran Aspal Beton - Aswad, Nurul; Megasari, Shanti Wahyuni; Saleh, Alfian (Universitas Jember, 2025)
Lignin is a cellulose substance contained in soft woody plants and can be used as a dispersing and stabilizing agent in asphalt extenders, dyes and concrete . Lignin can be easily found so it has the potential to become renewable energy. It is hoped that the use of lignin from plants can become a new innovation regarding environmentally friendly biomaterials. The aim of the research is to analyze the marshall characteristics of asphalt concrete mixtures. The research method used was an experimental study in the laboratory based on Bina Marga 2018 Revision II 2020. The research used variations in lignin substitution of 0%, 25%, 50%, 75% and 100% for filler weight. Before making the test object, the lignin that will be used as a filler replacement is first subjected to XRF testing to determine the level of lignin used. Marshall testing is carried out after soaking for 24 hours and then marshall testing at a temperature of 60â„ƒ. The research results showed that every 25% lignin substitution in the asphalt concrete mixture tended to increase the VIM and VMA parameters. For the stability parameters, flow, MQ and density tend to decrease with lignin substitution, but the results obtained still meet the 2018 Bina Marga Revision II 2020 requirements. In the VFWA and VITM parameters there are no variations that meet the requirements. The research conclusion is that lignin is not recommended as a substitute for filler in asphalt concrete mixtures.